Malaysian youth associations as places for empowerment and engagement - Krauss, Steven Eric; Zeldin, Shepherd; Abdullah, Haslinda; Ortega, Adriana; Ali, Zuraidah; Ismail, Ismi Arif; Ariffin, Zaifu (Elsevier, 2020)
Youth organizations often face challenges in reaching their potential as places of empowerment and engagement for youth development. While evidence-based practices of how organizations foster youth engagement exist, there are few replicable models or conceptual frameworks that cross-cut these different practices. The purpose of this multi-level, mixed methods study was to gain insight into how youth associations become empowering settings for youth engagement. Grounded in the theoretical perspective of empowered community settings, we sought to explore the links between national youth policy, the creation of empowering settings and youth engagement. Our focus was on Malaysia and its national network of youth associations. In Phase 1 of the study, thematic analysis of major policy documents revealed that Malaysian youth policy creates a shared belief system for the country’s youth associations according to three core themes: empowerment is intertwined with community capacity building; safety and inclusivity are paramount; and members are expected to be both teachers and learners as ‘partners in development’. In Phase 2, in-depth interviews with youth association leaders (N = 22; M age = 28; 68% male) highlighted the importance of a relational environment that includes opportunities to build social capital with adults and peers. The associations’ opportunity role structure further allows youth leaders to exercise voice in making decisions that mold the associations’ programs and allow the leaders to pass on knowledge and skills to younger members. In Phase 3, building on the findings from the first two study phases, a survey of regular association members (N = 262) indicated that safety and opportunities for personal growth predicted organizational engagement. For community engagement, as members moved outside of the confines of the organization and participated in community work, opportunities for personal growth remained central to engagement with social capital and adult support taking on additional importance. The study provides an initial conceptualization of best practices that link national policy and organizational leadership to participant engagement in youth associations.